Time variations of the Earth's gravity field and crustal deformation due to the establishment of the Three Gorges Reservoir - Zhang, K.; Featherstone, Will; Bian, S.; Tao, B. (Spinger-Verlag, 1996)
A method is developed with which to predict time variations of the Earth's gravity field and crustal deformation due to mass loading. Using this method, changes to the original geodetic datums can be estimated. This is applied to the Three Gorges area of China, due to the construction of the Yangtze river dam. Results indicate that the probable maximum crustal deformation and changes in gravity, elevation and deflection of the vertical will be 7.8mm, 4.7mgal, 19.0mm and 0.61 arc seconds, respectively. These changes are of importance for the establishment of monitoring operations both during and upon completion of the dam.